Decreased transthyretin predicts a poor prognosis in primary myelodysplastic syndrome - Chen, Ying; Niu, Tingting; Chen, Ting; Wu, Yue; Zou, Duobing; Shi, Cong; Wu, Ying; Zhang, Zhaoyi; Wu, Ningning; Zhang, Yi; Yan, Xiao; Sheng, Lixia; et al. (Frontiers in Nutrition, 2023)
Background This study aims to investigate the prognostic significance of transthyretin in newly diagnosed myelodysplastic syndromes (MDS). Methods The clinical, laboratory, and follow-up data of 280 newly diagnosed patients with MDS were collected. The relationship between serum transthyretin levels and overall survival (OS) and leukemia-free survival (LFS) were analyzed by Kaplan–Meier analysis and Cox Regression Model. Result In the MDS cohort, there were 121 cases in the low transthyretin group and 159 cases in the normal transthyretin group. MDS patients with decreased transthyretin had a higher risk score on the Revised International Prognostic Scoring System (IPSS-R) (p = 0.004) and on the molecular IPSS (IPSS-M) (p = 0.005), a higher frequency of TP53 mutation (p < 0.0001), a shorter OS (p < 0.0001) and LFS (p < 0.0001). Multivariate analyses showed that higher IPSS-R and IPSS-M score were adverse factors for OS (p = 0.008 and p = 0.015, respectively) and LFS (p = 0.024 and p = 0.005, respectively). Mutations of TP53 and NRAS were also poor factors for LFS (p = 0.034 and p = 0.018, respectively). Notably, decreased transthyretin was an independent adverse predictor for OS (p = 0.009, HR = 0.097, 95%CI, 0.017–0.561) but not for LFS (p = 0.167) when IPSS-R was included in the Cox regression model and an independent poor one for OS (p = 0.033, HR = 0.267, 95%CI, 0.080–0.898) and LFS (p = 0.024, HR = 0.290, 95%CI, 0.099–0.848) while IPSS-M involved. Conclusion The results indicate that decreased transthyretin could be an independent adverse prognostic factor in patients with MDS and may provide a supplement to IPSS-R and IPSS-M.